2011
DOI: 10.4314/ijbcs.v5i3.72283
|View full text |Cite
|
Sign up to set email alerts
|

Substitution de la farine de poisson par la farine d’asticots séchés dans le régime du rat en croissance : Risques pathologiques ?

Abstract: Tel (225) 66 52 92 38/ (225) 40 30 99 65 RESUME Deux groupes de dix rats en croissance sont nourris durant 15 jours, avec deux régimes alimentaires ne différant que par la qualité de leurs protéines animales. L'un contient 10% de farine de poisson (témoin) et l'autre, 10% de farine d'asticots séchés (FAS). Le dosage des paramètres biochimiques plasmatiques et la biométrie des reins et des foies sont effectués chez tous les rats en fin d'expérience. Aucune pathologie ni anomalie physiologique n'a été décelée… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
(5 reference statements)
0
5
0
3
Order By: Relevance
“…Elsewhere, the incorporation of dried bee meal into turkey starter diets at levels of 0 -30% linearly decreased the performance of the poults, an effect that was linked to the toxicity of bee venom (Salmon and Szabo, 1981). In Côte d'Ivoire, Bouafou et al (2011) showed that maggot meal could eliciting histological and histopathological damages. The study, which compared two groups of young rats fed with two diets containing 10% fish meal or 10% dried maggot meal for 15 d, showed a 6.6% decrease of the weight of the kidneys and 10.6% increase in the weight of the liver of rats fed on maggot meal.…”
Section: Toxicity Reactionsmentioning
confidence: 99%
“…Elsewhere, the incorporation of dried bee meal into turkey starter diets at levels of 0 -30% linearly decreased the performance of the poults, an effect that was linked to the toxicity of bee venom (Salmon and Szabo, 1981). In Côte d'Ivoire, Bouafou et al (2011) showed that maggot meal could eliciting histological and histopathological damages. The study, which compared two groups of young rats fed with two diets containing 10% fish meal or 10% dried maggot meal for 15 d, showed a 6.6% decrease of the weight of the kidneys and 10.6% increase in the weight of the liver of rats fed on maggot meal.…”
Section: Toxicity Reactionsmentioning
confidence: 99%
“…This loss of mass would be due to a very large protein deficit in diet, which would result in an indeterminate value of net ingested protein (PNU). According to [36], 9 to 18% of net protein ingested would promote weight gain in rats. Young rats fed the snail diet Limicolaria flammea (ESC) and the control diet (RTC) show an increase in rat weights.…”
Section: Discussionmentioning
confidence: 99%
“…and storage [20]. However, liver hypertrophy is an indicator of treatment-related abnormality [25,36]. Liver mass (3.19±0.96g) of rats fed snail feed (Limicolaria flammea) and rats fed herring fish (3.01±0.32g) (Clupea harengus) don't differ significantly (p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Ce qui justifie leur comportement de méfiance et de risque à minima étant donné que la perception des risques sanitaires et de la valeur nutritionnelle des aliments donne une nouvelle dimension à la notion de qualité et à sa signification (Papageorgiou, 2010). Au contraire, l'utilisation des asticots est une source appréciable de protéines animales qui améliore la valeur nutritive des animaux en croissance (Bouafou, 2007;Bouafou et al, 2011). Les farines d'asticots ont des teneurs en protéine brute de 50,4% MS, en lipide de 18,9% MS, en Calcium de 0,19% MS et en Phosphore de 1,60% MS (Makkar et al, 2014) comparables aux farines de viande, de poisson, de soja ou de coton, utilisées habituellement comme sources de protéines dans l'alimentation animale (Bouafou, 2007;Bouafou et al, 2011).…”
Section: Discussionunclassified
“…Au contraire, l'utilisation des asticots est une source appréciable de protéines animales qui améliore la valeur nutritive des animaux en croissance (Bouafou, 2007;Bouafou et al, 2011). Les farines d'asticots ont des teneurs en protéine brute de 50,4% MS, en lipide de 18,9% MS, en Calcium de 0,19% MS et en Phosphore de 1,60% MS (Makkar et al, 2014) comparables aux farines de viande, de poisson, de soja ou de coton, utilisées habituellement comme sources de protéines dans l'alimentation animale (Bouafou, 2007;Bouafou et al, 2011). Mieux, ces aviculteurs peuvent fonder leur perception sur les habitudes et les pratiques existantes.…”
Section: Discussionunclassified